New measurements of digital technology use: the Immersion in Digital Life and Quality of Digital Experience scales - Witowska, Joanna; Ogden, Ruth; Schoetensack, Christine; Goncikowska, Katarzyna; Wittmann, Marc; Černohorská, Vanda; Codina, Nuria; Martin-Soelch, Chantal; Fernández Boente, Mónica; Giner, Georgina; Pestana, José V.; Papastamatelou, Julie (Frontiers in Psychiatry, 2025)
IntroductionCurrent methods of assessing digital technology use fail to adequately capture a holistic picture of how individuals experience digital technology during daily life. This is because current measures focus on measuring the frequency/duration of specific forms of technology use or problematic use. This research aimed to create two general measures of digital technology use and experience, respectively, which are flexible amid technological changes.MethodsThe measured constructs were specified via bottom-up analysis of an international qualitative study (N=300) on post-covid digital practices. Across three studies we developed and validated the measures using data from 2227 participants.ResultsExploratory and Confirmatory Factor Analyses indicated that the Quality of Digital Experience Scale contains 26 items, measuring individuals’ perceptions and overall experience of digital technology usage and its impact on Well-being, Time and Efficiency, and Social Connectedness. The second scale, the Immersion in Digital Life Scale consists of five separate questions concerning individuals’ estimation of how much digital technology is present in different areas of life.DiscussionThe scales offer reliable measurements of individuals’ interactions with technology in the digital era. Their ability to capture engagement beyond frequency and duration will facilitate greater understanding of the complexities of the positive and negative impacts of digital practices on individuals and societies.